Processed meat consumption and lung function: modification by antioxidants and smoking. - Okubo, H; Shaheen, S; Ntani, G; Jameson, K; Syddall, H; Sayer, A; Dennison, E; Cooper, C; Robinson, S (European Respiratory Society, 2014)
Unhealthy dietary patterns are associated with poor lung function. It is not known whether this is due to low consumption of antioxidant-rich fruit and vegetables, or is a consequence of higher intakes of harmful dietary constituents, such as processed meat. We examined the individual and combined associations of processed meat, fruit and vegetable consumption and dietary total antioxidant capacity (TAC) with lung function among 1551 males and 1391 females in the UK in the Hertfordshire Cohort Study. Diet was assessed using a food frequency questionnaire. After controlling for confounders, processed meat consumption was negatively associated with forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and FEV1/FVC ratio in males and females, while fruit and vegetable consumption and dietary TAC were positively associated with FEV1 and FVC, but not FEV1/FVC ratio. In males, the negative association between processed meat consumption and FEV1 was more marked in those who had low fruit and vegetable consumption (p=0.035 for interaction), and low dietary TAC (p=0.025 for interaction). The deficit in FEV1/FVC associated with processed meat consumption was larger in males who smoked (p=0.022 for interaction). Higher processed meat consumption is associated with poorer lung function, especially in males who have lower fruit and vegetable consumption or dietary TAC, and among current smokers.